Push-Dose Pressors During Peri-intubation Hypotension in the Emergency Department: A Case Series - Abdullah Bakhsh (eScholarship Publishing, University of California, 2021)
Introduction: Emergency physicians frequently encounter critically ill patients in circulatory shock requiring definitive airway procedures. Performing rapid sequence intubation in these patients without blood pressure correction has lethal complications. Questioning the efficacy and fearing side effects of push-dose pressors (PDP) has created an obstacle for their use in the emergency department (ED) setting. In this case series we describe the efficacy and side effects of PDP use during peri-intubation hypotension in the ED. Case series: We included 11 patients receiving PDPs in this case series. The mean increase in systolic blood pressure was 41.3%, in diastolic blood pressure 44.3%, and in mean arterial pressure 35.1%. No adverse events were documented in this case series. Conclusion: The use of push-dose pressors during peri-intubation hypotension may potentially improve hemodynamic status when used carefully in the ED.